(untitled) (MAUSAM, 1990)
One dimensional simulation studies, with a vegetation canopy at the earth’s surface at two different locations in India, show that the soil moisture has a dominant role in regulating the strengths of the turbulent fluxes between the atmosphere and the around with or without vegetation. With vegetation, the boundary layer characteristics such as temperature profile get modified. The net warming of the atmosphere by the vegetation canopy depends on the amount of coverage and initial conditions. The calculated values of Bowen ’s ratio agree with observations.